Sidang Itsbat bagi Pasangan Nikah Siri Ditinjau dalam Perspektif Hukum Islam - Irpan Husein Lubis; Khairul Riza; Nicha Suwalla (Penerbit Goodwood, 2023)
Purpose: The purpose of writing this journal is to find out the implementation of itsbat trial determination for unregistered marriage couples in terms of Islamic law, and to know the judge's considerations in determining itsbat trial for unregistered marriage couples. Methodology: The method used is a normative approach, namely through library research, and an empirical approach, namely through field research by conducting a series of interviews with respondents and informants to obtain field data. Results: The results of the study show that the implementation of the determination of itsbat trial for unregistered marriage couples is reviewed in Islamic law, namely starting with the submission of an application for itsbat marriage by the applicant by completing certain requirements, and continuing with the implementation of itsbat trial to obtain a determination of itsbat trial. In its implementation there are requests that fall, are rejected and granted. The judge's considerations in determining itsbat for unregistered marriage partners are the need for the applicant's presence so that the marriage certificate is not aborted and shows evidence that the marriage has taken place legally in accordance with Islamic law in court.